Design and analysis of composite structures : with applications to aerospace structures - Kasapoglou, Christos (Aerospace series (Chichester, England), 2010)
Design and Analysis of Composite Structures enables graduate students and engineers to generate meaningful and robust designs of complex composite structures. Combining analysis and design methods for structural components, the book begins with simple topics such as skins and stiffeners and progresses through to entire components of fuselages and wings. Starting with basic mathematical derivation followed by simplifications used in real-world design, Design and Analysis of Composite Structures presents the level of accuracy and range of applicability of each method. Examples taken from actual.